CORPORATE GOVERNANCE DISCLOSURE PRACTICES AND FIRM’S FINANCIAL PERFORMANCE - Parvathy M. D , Dr. P. Balasubramanian (International Journal of Advanced Science and Technology, 2020)
The present study investigates the relationship between corporate governance and the overall financialperformance in the emerging Indian context. The relevance of corporate governance increased in theliberalized economic environment due to the integration of countries into the world market. Fast MovingConsumer Goods (FMCG) sector is India’s fourth largest industry, contributing almost 20 percent toGross Domestic Product (GDP). The study is to evaluate the influence of corporate governance in theoverall financial performance of the selected organizations in the FMCG sector. Corporate GovernanceDisclosure Index (CGDI), used for identifying the corporate governance compliance status and paneldata technique is used to investigate the extent of influence by corporate governance on the financialperformance.